PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) TERHADAP KARYAWAN PDAM BANDARMASIH KOTA BANJARMASIN - Zulbadi; Hastin Umi Anisah; Dahniar (Universitas Lambung Mangkurat, 2014)
The purpose of the reserch to identify and analyze the effect of transformational leadership and organizational commitment simultaniously and partially on the Organizational Citizenship Behavior. The method used is quantitative research that is explanatory, with a population of 324 people, technique sampling used is stratified random sampling with a sample of 81 people who serve as respondents, data analysis tool used is multiple linear regression using SPSS software ver.19.0. The results of this study are: Variable transformational leadership and organizational commitment positif and signification affect to the OCB with simultaneously and partially affect